2012
DOI: 10.2971/jeos.2012.12035
|View full text |Cite
|
Sign up to set email alerts
|

Microsized subsurface modification of mono-crystalline silicon via non-linear absorption

Abstract: We introduce a novel method of optically inducing microsized subsurface structures using non-linear absorption of near infrared light in mono-crystalline silicon. We discuss the physical processes such as multi-photon absorption and self focussing in the material. The results presented in this paper demonstrate a new method of subsurface modifications in silicon and may open up novel avenues for optical devices embedded in silicon and optical process for the separation of wafers from their ingots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
2
17
1
Order By: Relevance
“…However, no modifications could be created deeper inside silicon, when placing the focus inside the silicon layer [9]. Finally, evidence of subsurface damage was found in a recent study using an oil immersion objective with a numerical aperture of 1.25 [10]. However, despite the high numerical aperture, surface damage was reported [10].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, no modifications could be created deeper inside silicon, when placing the focus inside the silicon layer [9]. Finally, evidence of subsurface damage was found in a recent study using an oil immersion objective with a numerical aperture of 1.25 [10]. However, despite the high numerical aperture, surface damage was reported [10].…”
Section: Introductionmentioning
confidence: 98%
“…Similar to dielectric materials, internal modifications could be applied for the inscription of optical devices [9,10]. As silicon is the material of choice for the production of integrated circuits, this may allow electronics and optical components to be integrated on a single chip [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, subsurface modification of silicon by 1.55 lm lasers was reported, where nonlinear light absorption was utilized. 7,8 Sreenivas et al used an 800 fs laser at 1.55 lm to induce subsurface damage by initiating twophoton absorption and self-focusing. 7 Similarly, Verburg et al reported that silicon subsurface modification was achieved by using a 3.5 ns laser with a wavelength of 1.549 lm via two-photon absorption.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Sreenivas et al used an 800 fs laser at 1.55 lm to induce subsurface damage by initiating twophoton absorption and self-focusing. 7 Similarly, Verburg et al reported that silicon subsurface modification was achieved by using a 3.5 ns laser with a wavelength of 1.549 lm via two-photon absorption. 8 To the best of the authors' knowledge, the Er:YAG laser processing of silicon has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%